Implementing Sunda Local Wisdom-Based Education to Enhance Collaborative Learning in Ciptagelar Traditional Village, Sukabumi, Indonesia - Mirna Nur Alia Abdullah; Annisa Fadhilah (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
This research examines the integration of Sundanese local wisdom as a culturally grounded framework for collaborative learning in the Indigenous Village of Ciptagelar, Sukabumi. Using a qualitative approach and a systematic literature review to explore core cultural values, including sabilulungan (cooperation), ecological reverence, and customary practices. The findings show that incorporating these values can improve student engagement, socio-emotional development, and ecological awareness. The implementation is constrained by limited teacher training, a lack of contextual learning resources, and insufficient policy support. The study proposes a hybrid collaborative learning model that systematically involves indigenous community members as co-educators and employs contextualized learning modules grounded in Ciptagelar epistemologies. This model offers a structured way to bridge formal education with local knowledge systems and provides practical implications for educators and policymakers seeking sustainable, identity-affirming education rooted in local wisdom.